Using 320-slice perfusion computed tomography in visuali zation of prostate cancer - N. V. Sosnowski (Učenye Zapiski Sankt-Peterburgskogo Gosudarstvennogo Medicinskogo Universiteta im. Akad. I.P. Pavlova, 2016)
Visualization of prostate cancer remains an actual problem in urology and oncology. Purpose of the study – evaluation of prostate cancer visualization using 320-slice perfusion computed tomography (PCT). PCT results of 15 patients with suspected prostate cancer were evaluated. Studies were performed with the 320-slice spiral computed tomography Aquilion One (Toshiba, Japan). Perfusion of the prostate was calculated by the maximum gradient. Next, the areas of interest were placed on each perfusion map. For each of the areas of interest, the following indicators were calculated: the average blood flow velocity, normalized blood flow velocity, the difference of blood flow velocity in the contralateral areas of interest, the difference of the normalized blood flow velocity in the contralateral areas of interest. Differences between indexes depending on the results of histological examination for each area of interest were evaluated by the variance analysis and by pairwise comparison with the Tukey’s criterion. Statistical significance of differences was assessed by the specialized computer language R v 3.2, using pROC packets. Totally, 180 biopsies were obtained. 19 – prostate cancer Σ Gleason 6, 17 – prostate cancer Σ Gleason 7, 5 – prostate cancer Gleason Σ 8, 7 – inflammation, 121 – not pathological, 11 – prostatic intraepithelial neoplasia (PIN). The areas under the ROC curves for the studied parameters were: average blood flow velocity 0.6343, normalized blood flow velocity 0.5300, difference of blood flow velocity in contralateral areas of interest 0.5875, difference of normalized blood flow velocity in the contralateral areas of interest 0.6263. The results of our study shows low sensitivity of the method in detection of lowgrade prostate cancer.